Improving continuity of patient care across sectors: study protocol of a quasi-experimental multi-centre study regarding an admission and discharge model in Germany (VESPEERA) - Forstner, Johanna; Straßner, Cornelia; Weis, Aline; Uhlmann, Lorenz; Freund, Tobias; Peters-Klimm, Frank; Wensing, Michel; Kümmel, Stephanie; El-Kurd, Nadja; Rück, Ronja; Handlos, Bärbel; Szecsenyi, Joachim (BMC health services research, 2019)
Hospitalisations are a critical event in the care process. Insufficient communication and uncoordinated follow-up care often impede the recovery process of the patient resulting in a high number of rehospitalisations and increased health care costs. The overall aim of this study is the development, implementation and evaluation of a structured programme (VESPEERA) to improve the admission and discharge process.
Gesehen am 23.05.2019